When Chlorides are the Most Reactive: A Simple Route towards Diverse Mono- and Dicationic Dimethyl Phosphate Ionic Liquids - Priede, Elina; Bakis, Eduards; Zicmanis, Andris (Synlett, 2014)
Structurally diverse aromatic and aliphatic ionic liquids have been prepared via anion metathesis utilizing alkylammonium chlorides and trimethyl phosphate. Excellent oxygen-containing functional-group tolerance in preparation of potentially greener dimethyl phosphate ionic liquids has been demonstrated. For the first time, this method has been employed in the synthesis of dicationic imidazolium-based ionic liquids possessing a dimethyl phosphate counterion, providing a simple, direct route towards structurally novel products of high purity.
Keywords: monocationic ionic liquids; dicationic ionic liquids; anion metathesis; dimethyl phosphate